Nostra Aetate and the Spirit of Dialogue among Religious Believers in Larantuka City, East Flores - Dominikus Doni Ola; Ahmad Singgih Basuki; Yusuf Nataeli Lase (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2022)
This study analyzed the community interaction in Larantuka City, East Flores with the aim of determining the implementation of the Nostra Aetate document and the reciprocity between Muslims, Catholics, and Protestants. The qualitative data of this study were obtained from studies on documents and interviews with sources from Catholics, Muslims, and Protestants living in Larantuka. This study was conducted between January and June 2021. The researcher drew three conclusions from this study. First, Larantuka residents are open to accepting and acknowledging the presence of other religions besides Catholicism. Other religions are given the liberty to express their faith in Larantuka. Second, the Nostra Aetate document has been practiced, albeit not perfectly. The spirit of rivalry that grew among Catholics in the past is turning into a spirit of dialogue. Third, the “tulun talin" spirit, the Lamaholot customs and habits of supporting those in need or helping each other, which are the cultural background of the Larantuka people, serves as a way for the people to express the spirit of equal reciprocity among religious believers in Larantuka which Nostra Aetate inspired. The dominant attitudes are cooperation, mutual respect, and mutual acknowledgment that the presence and existence of other people with all religious and cultural backgrounds attached to them is a prerequisite for building human civilization and the common good.